The Influence of Intellectual Capital, Environmental Costs, and Environmental Performance of The Value of Manufacturing Companies Listed on Indonesian Stock Exchange - Ulfah, Yana; Purba, Alan Smith; Putri, Serli Amanda (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
This study aims to determine the influence of intellectual capital, environmental costs, and environmental performance on the value of manufacturing companies. The research method used in this study is multiple linear regression analysis. The population of this study consists of manufacturing companies in the basic materials industry sub-sector listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The research type used secondary data obtained from the official website of the Indonesia Stock Exchange and the official websites of the companies. The sample was selected using purposive sampling, resulting in a final sample of 20 companies that met the criteria. This study utilized the statistical data analysis program SPSS 27. The results of the hypothesis testing indicate that intellectual capital has a positive and significant effect on company value, environmental costs do not affect company value, and environmental performance has a positive and significant effect on company value.